Development and Characterization of Gamma Oryzanol Loaded Niosomes - Shubham Sharma; Budhram Saharan; Jinendra Sardiya; Vishvas Pathak (Current Research in Pharmaceutical Sciences, 2023)
Over the past several years, treatment of infectious diseases and immunization has undergone a revolutionary shift. Noisome are vesicles composed of non-ionic surfactants, which are biodegradable, relatively nontoxic, more stable and inexpensive, an alternative to liposomes. Noisome are of nonionic multilamellar vesicular structure of surface-active agents, which is similar to liposomes. This article highlights Ƴ-oryzanol (Oz) exert their antioxidant activity and often associated with lowering level of cholesterol, anti-inflammatory, anti-diabetic and anti-cancer effects. All reformulation studies were performed. The thin-film hydration technique was used for encapsulation of OZ in noisome. More than 85 % entrapment of Oz was achieved. Nearly 90 % drug was released within 24 hours. Formulation was found sterilized. Formulation was found stable after 5 weeks.